Facies model for a coarse-grained, tide-influenced delta : Gule Horn Formation (Early Jurassic), Jameson Land, Greenland - Eide, Christian Haug; Howell, John A; Buckley, Simon J.; Martinius, Allard W; Terje Oftedal, Bjørn; Henstra, Gijs A. (Sedimentology, 2016)
Acknowledgements: Funding for this project was provided from the Research Council of Norway through the Petromaks project 193059 and the FORCE Safari Project. Arild Andresen (University of Oslo) and Aka Lynge (POLOG) are thanked for logistical support, Björn Nyberg (Uni Research CIPR and University of Bergen) for assistance in the field, Arve Næss (Statoil) for providing data and assistance during the planning phase, Julien Vallet and Huges Fournier (Helimap Systems SA) for data acquisition. Riegl LMS GmbH is acknowledged for software support. We thank Brian Willis and an anonymous reviewer for their insightful and thorough reviews and Mariano Marzo for editorial comments. Peer reviewed